2009
DOI: 10.1007/s11207-009-9393-y
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Observations of Solar Wind Stream Interface Evolution

Abstract: The heliocentric orbits of the two STEREO satellites are similar in radius and ecliptic latitude, with separation in longitude increasing by about 45°per year. This arrangement provides a unique opportunity to study the evolution of stream interfaces near 1 AU over time scales of hours to a few days, much less than the period of a Carrington rotation. Assuming nonevolving solar wind sources that corotate with the Sun, we calculated the expected time and longitude of arrival of stream interfaces at the Ahead ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 23 publications
4
29
0
Order By: Relevance
“…If we assume that there is a significant distance between the fastto-slow and the slow-to-fast transitions, then the slow distribution functions also need to be taken into account, resulting in the additional contribution This interestingly enough reflects the well-established finding in observational data that the spectral intensities of ion distributions are inversely proportional to the bulk velocity of the solar wind (Hill et al 2009;Dayeh et al 2009b;Simunac et al 2009). …”
Section: Distribution Functions In the Presence Of Continuous Reinjecmentioning
confidence: 96%
“…If we assume that there is a significant distance between the fastto-slow and the slow-to-fast transitions, then the slow distribution functions also need to be taken into account, resulting in the additional contribution This interestingly enough reflects the well-established finding in observational data that the spectral intensities of ion distributions are inversely proportional to the bulk velocity of the solar wind (Hill et al 2009;Dayeh et al 2009b;Simunac et al 2009). …”
Section: Distribution Functions In the Presence Of Continuous Reinjecmentioning
confidence: 96%
“…Because the Sun's heliographic equator is tilted about 7 degrees with respect to the ecliptic plane, the separation in heliographic latitude between L5 and Earth can be more than 5 degrees. This relatively small latitude separation is potentially enough to result in substantially different stream structures at the two points of observation (Schwenn, 1990;Leske et al, 2008;Mason et al, 2009;Simunac et al, 2009). Simunac et al (2009) compared the expected and observed time delay between the observations of stream interfaces on STEREO/B and STEREO/A over heliographic longitude separations ranging from 2 to 48 degrees.…”
Section: Introductionmentioning
confidence: 99%
“…This relatively small latitude separation is potentially enough to result in substantially different stream structures at the two points of observation (Schwenn, 1990;Leske et al, 2008;Mason et al, 2009;Simunac et al, 2009). Simunac et al (2009) compared the expected and observed time delay between the observations of stream interfaces on STEREO/B and STEREO/A over heliographic longitude separations ranging from 2 to 48 degrees. They found significant deviations from the expected time-of-arrival when the spacecraft were separated by more than 20 degrees of longitude.…”
Section: Introductionmentioning
confidence: 99%
“…Several weak CMEs were seen by LASCO (reported on the CDAW CME catalogue) and at least four CIRs were reported in more-detailed analyses of STEREO/PLASTIC in situ data by Simunac et al (2008).…”
Section: Discussion and Summarymentioning
confidence: 96%
“…We do not know exactly why this is, given that at both other spacecraft locations (Wind and STEREO-B) the density compares well, but clearly the density peak does not appear to be manifest from STEREO-B to Wind to STEREO-A as one might expect for a co-rotating dense structure. Simunac et al (2008) note that there are some CIRs during this interval where the estimated time of arrival from one STEREO spacecraft to the other (under the assumption of radial flow) is not consistent with actual arrival times. This discrepancy could result from potential changes in the solar wind speed/make-up or motion (or changes) of the coronal hole on the solar surface responsible for generating the CIR feature.…”
Section: Comparison With Stereo/plasticmentioning
confidence: 91%